MORPHOMETRIC AND HISTOCHEMICAL RESEARCH OF MELISSA OFFICINALIS L. HERB FROM THE COLLECTION OF NIKITSKY BOTANIC GARDEN - A. S. Nikitina; L. A. Logvinenko; N. V. Nikitina; S. A. Nigaryan (Фармация и фармакология (Пятигорск), 2019)
The article presents the results of morphological-anatomical, morphometric and histochemical studies of the aerial part of Melissa officinalis L., a selection variety sample from the collection of Nikitsky Botanical Garden – National Science Center (NBG-NSC) of the Russian Academy of Sciences, Republic of Crimea. The data on the morphology, histochemistry and morphometry of the main diagnostic microscopic signs of the Melissa officinalis L. herb, which are crucial for establishing the authenticity of medicinal plant materials, and also show the localization of secretion of metabolites and the heterogeneous nature of Melissa essential oil, have been obtained.The aim. Is to determine the microdiagnostic signs and biometric characteristics of the Melissa officinalis L. variety sample, introduced in Nikitsky Botanical Garden, to study the possibility of using histochemical reactions for the analysis of tissues and secretory structures of the studied species.Materials and methods. The plant material was provided by Nikitsky Botanical Garden. The study of microscopic signs, morphometric characteristics as well as histochemical tests, were performed according to the methods of the State Pharmacopoeia of the Russian Federation, XIII edition, using a Micromed-1 light microscope, a Micromed Micrometer 3 LUM fluorescent microscope and a Digital Eyepiece microscope camera MD 3.2 digital camera. The photos were edited in the program Paint. NET.3.5.11.Results. The main diagnostic microscopic signs of the herb of the Melissa officinalis L. selection variety sample can be called as follows: simple unicellular conical, nonbranching hairs, simple multicellular conical hairs, capitate hairs with a multicellular leg and a funnel-shaped head and with a unicellular leg and a spherical head, essential oil glands of a radial-type with 6-8 excretory cells. These signs have been diagnosed in the crushed raw materials. A quantitative assessment of the morphological and anatomical signs of the leaf (leaf thickness, height of the cells of the upper and lower epidermis, stoma density per 1 mm2 of the epidermis), stem, calyx and corolla was carried out. The size of cells, stoma, trichomes, as well as the frequency of the location of trichomes have been analyzed, too. The presence and localization of lipids, polysaccharides, phenolic compounds, flavonoids, essential oil, terpenoids, alkaloids in tissues and trichomes of the herb have been studied by histochemical methods using light and fluorescent microscopy.Conclusion. Morphological and anatomical study of the herb of the Melissa officinalis L. selection variety sample from the Nikitsky Botanical Garden collection has been carried out, diagnostically significant microscopic signs of raw materials have been revealed and their biometric characteristics have been established. For the first time the localization of characteristic secreted biologically active substances in the tissues and secretory structures of the herb has been studied by histochemical methods. The results of the experimental studies complement the scientific literature data and can be used to confirm the authenticity, identification and standardization of the aerial parts of this variety sample.